“Judicial Control Over The Appropriateness Of The Legislator’s And The Administrative Authorities’ Use Of The Discretionary Power” - Badran, Dr. Duaa Mohammed Ibrahim (The journal of contemporary issues in business and government, 2021)
The study investigated the issue of judicial control over the appropriateness of the administration’s use of its discretionary power. The idea of appropriateness is the instrument through which the judiciary exercises control over the use of the discretionary power by the entity to which the system authorized it, as well as the appropriateness of the measures taken in some aspects in which the legislator granted the discretionary power for an entity to take the appropriate actions it deems appropriate. The judiciary, through this control, can achieve a balance between what actions are taken and what the legal centers related to such actions can be affected therewith. This control is conducted with no specific controls for the idea of appropriateness in general, but it is applied to each case separately, and then it is reviewed by the judicial authority unilaterally. The criterion of appropriateness is that the action that was conducted in accordance with the powers granted to a certain entity does not exceed the achievement of the intended goal, and did not abuse, overuse or underuse the powers granted to it by the legislator, and that the use of the said discretionary power was merely for the benefit of the public interest, according to the circumstances surrounding each time the entity uses its discretionary power. Actually, the idea of appropriateness is a changing idea, so the legal actions which are taken according to what the legislator has authorized any entity of whatsoever discretionary power, must be subjected to the judicial control according to the criterion of appropriateness.